GENETIC DIVERSITY STUDIES AMONG DIFFERENT MORPHOPHYSIOLOGICAL TRAITS IN SPRING WHEAT (TRITICUM AESTIVUM L.) IN RELATION TO HEAT TOLERANCE - SMITA WAIKER,; B. ARUN, (The Bioscan, 2015)
The present investigation in fifty wheat (Triticumaestivum L.) genotypes was undertaken to study the genetic variability and selection response for heat tolerance through measuring canopy temperature depression and chlorophyll content as selection criterion at various crop growth stages. Wide genetic diversity was observed among the accessions which were grouped into eight clusters by Tocher’s method based on D2 values.The intra- cluster distances were lower in all cases reflecting homogeneity in genotypes within the clusters.The cluster V contained the maximum numbers of genotypes (11) and cluster III had the minimum number of genotypes (2). The highest intra-cluster distance was observed in cluster III (228.132) that represented maximum variability within the cluster and Cluster VII (68.365) had the lowest intra-cluster distance. The maximum inter cluster distance was noticed between the clusters II and VIII(1154.262) and the lowest between clusters VI and VII (165.073). Cluster with large distances were considered more diverged than those with small distances.The major contributing character towards genetic divergence was found to be plant height (24.82%) followed by grains per spik (21.39%), chlorophyll content (16.57 and 19.10) and spikelets per spike (6.12). Abbrivations: CTD-canopy temperature depression, PCA-principle component analysis, CVA- conical vector analysis, PCO- principle coordinate analysis.